Summer Cyclones and Their Association With Short-Term Sea Ice Variability in the Pacific Sector of the Arctic - Finocchio, Peter M.; Doyle, James D. (Frontiers in Earth Science, 2021)
We investigate the effects of summer cyclones on sea ice within the Pacific sector of the Arctic by analyzing the surface energy flux and wind forcing from a large sample of cyclones. Consistent with recent studies, we find that cyclones earlier in the melt season tend to be associated with less 1-5 day sea ice loss than what occurs in the absence of cyclones. In contrast, cyclones later in the melt season slightly accelerate the 1-day sea ice loss. The reduced ice loss following cyclones in June is primarily due to increased cloud cover reducing the net shortwave flux at the surface. Clouds associated with cyclones in July and August also reduce the net shortwave flux at the surface, but only over high-concentration sea ice. Southerly winds associated with August cyclones increase both the negative local sea ice advection and the surface heat flux, particularly for the low concentration sea ice that is prevalent in August. Sea ice advection and surface heat flux are the only two factors we examined that can explain the enhanced ice loss on cyclone days in August. We also examined two cyclone cases that impacted sea ice in the East Siberian Sea in June 2012 and August 2016, and found for both cyclones that the sensible heat flux is the largest positive anomalous forcing and the shortwave radiative flux is the largest negative anomalous forcing. Similar to the large sample of cyclones, the shortwave flux has a stronger relationship to local changes in SIC in June than in August. Part of the reason for this is that the cloud shortwave radiative forcing during the August cyclone is 26% weaker than during the June cyclone. In an area averaged sense, the anomalous surface energy and wind forcing of both cyclone cases is similar in magnitude, yet the August cyclone is followed by a greater reduction in both sea ice area and mean sea ice concentration than the June cyclone. This result emphasizes how the underlying sea ice characteristics largely determine cyclone impacts on sea ice on short time scales.